2020
DOI: 10.37934/araset.21.1.4151
|View full text |Cite
|
Sign up to set email alerts
|

Radiative Boundary Layer Flow of Casson Fluid Over an Exponentially Permeable Slippery Riga Plate with Viscous Dissipation

Abstract: This study is aimed to analyze the steady of stagnation point flow and radiative heat transfer of a non-Newtonian fluid which is Casson fluid passing over an exponentially permeable slippery Riga plate in presence of thermal radiation, magnetic field, velocity slip, thermal slip, and viscous dissipation effects. The governing partial differential equations are transformed into ordinary differential equations by using similarity transformation then solved numerically by boundary value problem solver (BVP4C) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Hayat et al [31] have elaborated on magneto-hydrodynamic Casson fluid under variable properties and with viscous dissipation. Yusof et al [32] discussed the exponentially slippery Riga plate with viscous dissipation in radiative boundary layer flow of Casson fluid. Loganathan and Rajan [33] have introduced optimization of the entropy of Williamson fluid with joule heating and zero mass flux of nano-particles.…”
Section: Introductionmentioning
confidence: 99%
“…Hayat et al [31] have elaborated on magneto-hydrodynamic Casson fluid under variable properties and with viscous dissipation. Yusof et al [32] discussed the exponentially slippery Riga plate with viscous dissipation in radiative boundary layer flow of Casson fluid. Loganathan and Rajan [33] have introduced optimization of the entropy of Williamson fluid with joule heating and zero mass flux of nano-particles.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to indicate a number of relevant and practically important tasks where such models are used, such as in the studies by Khan et al, [2], Aabid et al, [3], Traub [4], and Yusof et al, [5]. In particular, in computational aerodynamics, pointed wedges are used to generate shock waves [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yusof et al, [26] investigates numerical stagnation point flow and radiative heat transfer of a non-Newtonian fluids through slippery Riga plate with the effects of thermal radiation, magnetic field, velocity and thermal slip, and viscous dissipation. And they have been found that temperature decreases when the velocity slip parameter and thermal slip parameter are increased.…”
Section: Introductionmentioning
confidence: 99%